Micropropagation of Clerodendrum indicum (L.)Kuntze: An Unexplored Medicinal Plant - ANINDITA MUKHERJEE; SIKHA DUTTA; ABHIJIT BANDYOPADHYAY (International Journal of Pharma and Bio Sciences, 2012)
A simple micropropagation protocol has been achieved using nodal region and apical leaf of Clerodendrum indicum,(L) kuntze; an important medicinal plant of Verbenaceae. The explants were cultured in MS medium supplemented with NAA, BA, 2,4-D,Kn, IBA in various combination and concentrations (0.1- 10.0 µM). Response to callogenesis were diverse, ranging from white vigorous compact callus (1.0µM NAA), compact green calli in NAA:BA( 0.5:0.1µM) & (1.0:1.0 µM ), white compact calli (1.0:3.0µM) NAA: Kn. Only 2,4D expectedly generated profuse watery, vigorous, friable calli (1.0µM).The nodal region was differentiated into shoot directly in combinations with NAA and BA(0.1:1.0µM, 1.0:3.0µM, 0.5:1.0µM, 0.1:0.5µM). Multiple shooting were generated in NAA: BA combination (0.5:0.3µM). Moderate rooting were initiated at high IBA level in (10 µM) in full strength MS Medium. Simultaneous emergence of root & shoot were noticed from callus in triple combination of NAA, BA and IBA,in triple combination(5.0:1.0:1.0µM). The well rooted plant were transferred in the sterile soilrite covered with polybag in the culture room for acclimatization for 15 days. Such plants were transferred into the pot with 90% survivality.This is the maiden report of micropropagation of Clerodendrum indicum(L.)Kuntze.